A Responsibility to the World Saramago, Politics, Philosophy - Baltrusch, Burghard; Salzani, Carlo; Vanhoutte, Kristof (iBroLiT - Estudos Iberorrománicos de Literatura e Tradutoloxía / Ibero-Romance Studies in Literature and Translatology, 2023)
In a 1987 interview, José Saramago eloquently expressed what could be considered his political-philosophical manifesto: "Human beings should not content themselves with the role of mere observers. They bear a responsibility to the world; they must actively engage and intervene." In 1998 the celebrated writer was honoured with the Nobel Prize for Literature. So Saramago did not only as a human being and a citizen, but also as an artist refuse to be a passive observer. Despite his profound and always critical pessimism, he tirelessly propelled both his public and artistic persona toward impactful actions and interventions, showcasing an unwavering dedication to reshaping the world. This volume seeks to delve into this facet of his legacy, exploring it from diverse political and philosophical perspectives.